(untitled) (Patan Pragya, 2022)
Anthropologists and Nepali cultural historians and literates, including Tibetologists and South Asian cultural historians have commonly conceptualized Himalayan peoples and their civilization as an “Indo-Tibetan Interface ∕ ” Consequently, the Himalayan peoples have been explained within very generic terms given by their neighbors, scholars, and then state administrators such as Kiratiand Bhote. This review article also shows that using such generic terms Kirati and Bhote are a little problematic because these terms have been used in a way that emphasizes many differences as if they have nothing in common. In his review article, I argue that understanding Kirati and Bhote people requires a perceptive of common racial, religious, cultural, and historical origin, rather than dichotomizing them. Thus, Bhote and Kirati might have come to be used as ethnic names in the same sense and purpose as Edward Said (1978) identified how Westerners used “binary grammar” to describe “the Orient” to them. Thus, it will not result in pinpointing any ethnic group, present or in past. I argue that both Kirati and Bhote are not specific ethnonyms and not the only ones of this kind and are referential terms of a most general kind, perhaps like paharia.